(untitled) - Clarkson, Mark (San Francisco, 2004)
This book throws you right into the thick of things, dropping you ringside for a series of digital duels and artistic collaborations. In this groundbreaking guide top artists challenge each other in a series of Photoshop Tennis matches—and you get to peer over their shoulders. You'll watch them put Photoshop through its paces, creating incredible new work under grueling deadlines. You'll see which tools and techniques they use, and how and why they choose them when the clock is ticking and the world is watching.
Keywords: Computer graphics,Đồ họa vi tính